Cytoprotective Effects of Melatonin Against Amitriptyline-Induced Toxicity in Isolated Rat Hepatocytes - Shohreh Taziki; Mohammad Reza Sattari; Siavoush Dastamalchi; Mohammad Ali Eghbal (Tabriz University of Medical Sciences, 2015)
Purpose: Amitriptyline, one of the commonly used tricyclic antidepressants, caused rare but severe hepatotoxicity in patients who received it continuously. Previous findings showed that the intermediate metabolites of amitriptyline produced by CYP450 are involved in hepatic injury. Melatonin is an antiaging and antioxidant hormone synthesized from pineal gland. The aim of present study was to evaluate the protective role of melatonin in an in vitro model of isolated rat hepatocytes. Methods: Markers such as cell viability, reactive oxygen species formation, lipid peroxidation, mitochondrial membrane potential, and hepatocytes glutathione content were evaluated every 60 minutes for 180 minutes. Results: Present results indicated that administration of 1mM of melatonin effectively reduced the cell death, ROS formation and lipid peroxidation, mitochondrial membrane potential collapse, and reduced cellular glutathione content caused by amitriptyline. Conclusion: Our results indicated that melatonin is an effective antioxidant in preventing amitriptyline-induced hepatotoxicity. We recommend further in vivo animal and clinical trial studies on the hepatoprotective effects of melatonin in patients receiving amitriptyline.